Efektivitas Pengendalian Kumbang Tanduk (Oryctes rhinoceros) dengan Bahan Alami Mengkudu dan Air Nira pada Tanaman Belum Menghasilkan (TBM) Kelapa Sawit PT Bakrie Sumatera Plantations Tbk. - Sigit Setiawan Pelix; Henry Budi Hasibuan (Jurnal Ragam Pengabdian, 2026)
The rhinoceros beetle (Oryctes rhinoceros) is one of the main pests in immature oil palm plants (IMP) which can cause damage to growing points and reduce plant productivity. Control that still relies on chemical insecticides has the potential to increase costs and impact the environment. This study aims to determine the effectiveness of using natural ingredients of noni fruit (Morinda citrifolia) and palm sap as attractants in controlling rhinoceros beetle pests in IMP oil palm plants. The study was conducted at PT Bakrie Sumatera Plantations Tbk using a nonfactorial Randomized Block Design (RBD) with 9 treatments and 4 replications. Observations were made on the number of rhinoceros beetles trapped and the level of pest attack before and after trap application. The results showed that the use of noni and palm sap was able to attract and trap O. rhinoceros effectively. The best treatment was obtained at P8 (150 grams of noni fruit) with an average catch of 5.89 individuals/week. The use of traps also reduced the rhinoceros beetle infestation rate from 0.64% to 0.34%, a 47% decrease. The use of these natural materials has the potential to be an environmentally friendly control alternative and reduce reliance on chemical insecticides.